(untitled) (Journal of Pharma Insights and Research, 2025)
Nerium oleander (Apocynaceae) is a valuable medicinal plant with several pharmacological properties. It has gained a lot of attention for its extensive traditional uses and potential therapeutic applications. Phytochemical analysis shows the presence of bioactive compounds including cardiac glycosides, terpenoids, flavonoids, and phenolic compounds. The plant exhibits pharmacological activities such as antimicrobial, antidiabetic, anticancer, and anti-inflammatory properties. Traditional medicine systems across various regions have utilized different parts of N. oleander for treating conditions ranging from cardiac disorders to skin ailments. However, the plant’s therapeutic potential is counterbalanced by significant toxicity concerns due to the presence of cardiac glycosides, particularly oleandrin and nerine. These compounds can cause severe cardiovascular complications and gastrointestinal disturbances. Recent research has revealed the molecular mechanisms underlying both therapeutic effects and toxicity profiles. The effects of Nerium oleander on various organ systems, including cardiac, hepatic, and renal tissues, have been documented through experimental studies. Modern analytical techniques have identified specific bioactive compounds responsible for both beneficial and adverse effects. The growing scientific evidence supports traditional therapeutic applications while emphasizing the critical need for careful consideration of safety parameters in medicinal use